Innovative and Creative Strategies for the Pempek Business in Penetrating the International Market - Tri Sinarti; Sudarmiatin Sudarmiatin; Rosmiza Bidin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The success of MSMEs in the internationalization process cannot be separated from business strategy, in the form of creative and innovative strategies which are the methods used by companies to expand and sell products/services outside their domestic market. This research aims to analyze the creative and innovative strategies carried out by Pempek Syamil Palembang. The research method used in this research is a qualitative descriptive research method. Facts in the field are the main focus in this research, by describing them in as much detail as possible based on these facts. Through this research, the author succeeded in finding that the creative and innovative strategies implemented by Pempek Syamil cover all dimensions of innovation and creativity, namely product, process and marketing. The hope is that through this research, Pempek Syamil Palembang can continue to expand its presence in the international market. In conclusion, innovative and creative strategies are not just a necessity, not just a trend, but an urgent need for modern business and are a necessity and also the main key to winning business competition and sustainability in the international market. By prioritizing innovation and creativity in every aspect of business, entrepreneurs can create significant added value, build competitive advantages, and achieve long-term success in this competitive entrepreneurial world.